Analisis Preeklampsia Ibu Hamil pada Masa Pandemi Covid-19 di Puskesmas Sepatan Kabupaten Tangerang Tahun 2021 - Yenny Aulya; Vivi Silawati; Wulan Safitri (Universitas Baiturrahim, 2021)
Medical record data at the Sepatan Health Center in 2019 showed that the incidence of preeclampsia from 735 deliveries was obtained as many as 93 people (12.65%) pregnant women who underwent examinations in the January-December 2020 period, and increased to 116 people (13.25%) from 875. childbirth, and in January 2021 there were 35 preeclampsia of pregnant women and 81 preeclampsia of pregnant women, out of 875 deliveries. Analyzing factors associated with preeclampsia of pregnant women during the Covid-19 pandemic at the Sepatan Public Health Center, Tangerang Regency in 2021. Methods This type of research is an analytical survey research, with a cross sectional approach. This population is all pregnant women who experience preeclampsia in January 2021 as many as 35 respondents, using a total sampling technique of 35 respondent’s pregnant women with preeclampsia. The results showed that five variables were statistically proven to have a significant relationship with the incidence of preeclampsia, namely age (p = 0.010 <0.05), parity (p = 0.021 <0.05), history of disease (p = 0.004 <0, 05) multiple pregnancy (p = 0.026 <0.05) and nutritional status (p = 0.007 <0.05). There is a significant relationship between age, parity, history of disease, multiple pregnancies and nutritional status on the incidence of preeclampsia of pregnant women at the Puskesmas Sepatan, Tangerang District in 2021. For midwives to be more observant in examining preeclampsia, especially age (<20 years or> 35 years), mothers who are pregnant for the first time, have a history of disease, pregnancy with multiple fetuses and nutritional status who are overweight in pregnant women